Probabilistic assessment of power system mode with a varying degree of wind sources integration - Rahmanov, Nariman; Kurbatskiy, Viktor; Tomin, Nikita; Mammadov, Zaur; Guliyev , Huseyngulu (EDP Sciences, 2017)
At present among renewable sources the wind and solar plants have the most significant portion of power generation. Randomly changing and intermittent nature of this power leads to the stochasticity of the power grid mode, estimation of parameters of which requires application of probabilistic modeling. In the paper it is proposed an advanced algorithm of probabilistic load flow based on the development of two-point estimation method, the efficiency of which is confirmed on the basis of computational experiments and comparative analysis of the Monte Carlo simulation results. Calculationsand analysis of the modeling results were carried out on standard 14-nodal scheme of IEEE and real electrical network of “Azerenerji” Grid.